Youth Employment, Recruitment and a Youth-Targeted Wage Subsidy : Findings from a South African Firm Level Survey - Schoer, Volker; Rankin, Neil (World Bank, Washington, DC, 2017)
Employment issues are the most serious problems facing South Africa currently. Among these are the problems of unemployment, as well as underemployment or lack of decent work for the already employed, compounded by labour markets that are generally less than efficient in job search and matching. Unemployment in South Africa, by narrow standards, is approximately 25 percent, an extraordinarily high level, made even more worrying by its stagnancy or growth at different times over the past decade. However, although such levels of unemployment have detrimental effects on all members of society, they do affect groups differentially. Thus, unemployment rates are consistently, significantly higher for women, Africans, people from rural areas, and the less educated. Unemployment is highest, too, amongst the youth in South Africa, and much higher than international norms, despite rising unemployment amongst youth globally in the past decade. In South Africa, youth is officially defined as people aged between 14 and 35 years old; however, this is not in line with international definitions, which usually demarcate the 16 to 24 year old group. The aim of this paper is therefore to shed some light on the employment process of young South Africans and to investigate firm level responses to the implementation of a targeted hiring voucher for young job seekers aged 20-24. The first section of the paper outlines the conceptual framework used to investigate factors that determine employment of young workers and the impact of a targeted wage subsidy. The second section presents findings from a firm survey illustrating the firm characteristics that are associated with employing young workers and responses to a hypothetical wage voucher. The third section discusses the findings in the light of the theory while the fourth section concludes.